Sulfasalazine as a Corrosion Inhibitor on Carbon Steel Metal Surfaces in Acidic Media Using the Hydrogen Evolution Method: Experimental and Theoretical Studies - Obaid, Hadi Thamer; Mutar, Muthanna Mahmood; Ali, Safaa Hussein (Indonesian Journal of Chemistry, 2025)
Current study designed to explore the anti-corrosion effect of 2-hydroxy-5-{(E)-[4-(pyridin-2ylsulfamoyl)phenyl]diazenyl} benzoic acid (sulfasalazine, SSZ) on carbon steel. 1 M of HCl solution used as an aggressive medium. The corrosion process was significantly inhibited by SSZ using simple, direct and accurate method (hydrogen evolution) to measure corrosion inhibition process. The results showed that the corrosion inhibition efficiency increased with increasing the inhibitor SSZ concentration. Three different concentrations of the inhibitor SSZ (0.1 × 10−3, 0.5 × 10−3, and 1.0 × 10−3 M) were used in the corrosion experiment. Results showed a maximum inhibition efficiency (89.74%) achieved at the concentration of 1 × 10−3 M and the temperature of 308 K. The calculations of the hydrogen evolution method showed that the investigated SSZ acted as a mixed-type inhibitor. Adsorption of SSZ on the carbon steel surface obeys the Langmuir adsorption isotherm. The quantitative chemical parameters were calculated using density functional theory (DFT). In addition, full geometry optimizations were performed using DFT with B3LYP. The correlation between the theoretical and experimental results is discussed. The theoretical and experimental studies showed that SSZ is a good inhibitor as the maximum anti-corrosion activity was achieved at the highest concentration of the SSZ (1 × 10−3 M), and the lowest temperature used in the experiment.